Digital Transformation in Improving Teacher Performance: A Quantitative Study of Digital Leadership, Digital Culture, and Innovation - Wiwik Pudjaningsih; Nur Intan Rochmawati; Lisa Virdinarti Putra; Zuhri Saputra Hutabarat; Heni Pratiwi (Dinasti Publisher, 2026)
This study aims to examine and demonstrate the impact of digital leadership, digital culture, and innovation on enhancing teacher performance, as well as the degree to which technology use and innovative teaching methods spearheaded by school administrators can enhance learning efficacy. The study involved 110 teachers from State Vocational High Schools in Jambi City of this study, using a quantitative ex post facto design. Data were collected using validated questionnaires to gather data. The evaluation stage of the measuring model and the structural model, as well as assessing direct and indirect influences, were used to analyze the data. The results indicate that digital leadership, digital culture, and innovation significantly influence teacher performance, lack adequate training, lack technology adoption, and less competent leaders, 2) Teachers who are in an environment with a strong digital culture tend to be more innovative in designing learning, 3) Teacher innovation creates new ideas in learning, teachers use creative learning models, and teachers utilize technology, 4) Lack of organizational readiness in adopting technology, poorly planned innovation, and lack of digital competence of leaders, 5) Teachers who are familiar with technology tend to find new ideas more easily, utilize online learning platforms.